Association analysis of dry heat or wet cold weather and the risk of urolithiasis hospitalization in a southern Chinese city - Yanlu Li; Xubiao Duan; Shichen Wan; Xiaoning Wang; Yanbin Hao (Scientific Reports)
Abstract To analyze the relationship between hot or cold, and wet or dry interacting weather, and urolithiasis-related hospitalizations. Distributed lag nonlinear model for time series design was used to build exposure-response curves for the association of daily mean temperature and relative humidity with urolithiasis-related hospitalizations. Cut-off values were determined for temperature, humidity, and dichotomous categories to define heat-cold and wet-dry meteorological conditions. Based on a total of 38,184 urolithiasis-related hospitalizations from 2018 to 2019 in Ganzhou as a large prefecture-level city in southern China, dry-heat weather during the hot season (May to September) increased the risk of urolithiasis-related hospitalizations (relative risk [RR]: 1.17, 95% confidence interval [CI]: 1.02, 1.35), with the most pronounced effects in those aged 21–40 years and male. Wet-cold weather in the cold season (December to February) increased the risk of urolithiasis-related hospitalizations in the total population (RR: 1.58, 95% CI: 1.20, 2.07). The effect was significant in the 21–60 years old age and both genders groups. Both dry-heat weather in the hot season and wet-cold weather in the cold season could trigger urolithiasis.